Adjuvant effects of killed Lactobacillus casei DK128 on enhancing T helper type 1 immune responses and the efficacy of influenza vaccination in normal and CD4-deficient mice. Issue 36 (10th August 2020) - Jung, Yu-Jin; Kim, Ki-Hye; Ko, Eun-Ju; Lee, Youri; Kim, Min-Chul; Lee, Young-Tae; Kim, Cheol-Hyun; Jeeva, Subbiah; Park, Bo Ryoung; Kang, Sang-Moo
Abstract: Lactic acid bacteria Lactobacillus casei DK128 isolated from fermented vegetable foods was suggested to stimulate innate immune responses. Here, we investigated whether heat-killed DK128 would exhibit adjuvant effects on enhancing the efficacy of influenza vaccination. Immunization of mice with split influenza virus vaccine in the presence of heat-killed DK128 induced significantly higher levels of both IgG1 and IgG2c isotype antibodies than those by vaccine only. A single dose DK128-adjuvanted influenza vaccination conferred higher efficacy of protection, as evidenced by intact lung function, less weight loss, enhanced clearance of lung viral loads, and lower levels of inflammatory cytokines and infiltrates. Immunization of CD4 T cell-knockout (CD4KO) mice with influenza vaccine and DK128, but not with vaccine alone, induced isotype-switched IgG antibodies and protection against lethal challenge in CD4KO mice. The results in this study suggest heat-killed DK128 as a potential vaccine adjuvant, promoting the induction of IgG isotype switching in CD4-deficient condition and enhancing protective efficacy of split influenza vaccination in immunocompromised and immune-competent subjects.